Pengembangan Campuran Komposisi Bahan Baku pada Perusahaan Daur Ulang Plastik Berjenis PVC PT. RJM - Yunus Alfian (Jurnal Titra, 2020)
PT. RJM is a carpet manufacturing company made from recycled polyvinyl chloride (PVC) plastics. The raw materials used by the company are taken by suppliers from the waste products of other companies which also use PVC raw materials such as shoes, raincoats, food packaging, children's toys, plastic bags, etc. The company is developing a mixture of raw material compositions by adding other alternative raw materials so that the products produced have better quality. In this study the author proposes the addition of cable skin made of PVC. This study discusses the effect of improving product quality by adding PVC cable skin to a new mix of compositions, the cost of using a mixture of old and new compositions, challenges faced by companies both in the use of a mixture of new compositions and mechanical recycling, and recommendations to companies about the shortcomings in the process of managing the recycling of polyvinyl chloride (PVC) by mechanical recycling.